The spectroscopic orbits and other parameters of the symbiotic binary FN Sgr - Brandi, Estela (2005)
We present a study of the eclipsing symbiotic binary FN Sgr with a period of 568.3 days determined photometrically and confirmed spectroscopically. The hot component underwent a 2.5 mag eruption covered by most of our spectroscopic observations. In particular, we have determined for the first time spectroscopic orbits based on the radial velocity curves for both components. A set of blue absorption lines resembling an A-F type star is present in all our spectra and they seem to be associated with the hot component. Based on the light curve, we derive the red giant’s radius (140 R ☉) and the orbital inclination (i = 80◦). We find that FN Sgr is similar to other S-type symbiotic binaries, composed by an M 5-type giant (M g = 1.5 M ☉ ) and a hot white dwarf (M h = 0.7 M ☉ , R h = 0.2 R ☉ ) with a binary separation of ∼1.6 AU. The red giant is just filling its Roche lobe and a geometrically and optically thick accretion disk is likely to be present around the low-mass accretor. The evolution of Th and Lh along the active phase argues in favour of accretion disk instabilities similar to those of Z And. We have also studied spectral changes and photometric variations as a function of both the hot component activity and the orbital motion.